2015
DOI: 10.1002/chem.201405480
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Anisotropy in “Scorpionate” First‐Row Transition‐Metal Complexes: A Theoretical Investigation

Abstract: In this work we have analyzed in detail the magnetic anisotropy in a series of hydrotris(pyrazolyl)borate (Tp(-)) metal complexes, namely [VTpCl](+), [CrTpCl](+), [MnTpCl](+), [FeTpCl], [CoTpCl], and [NiTpCl], and their substituted methyl and tert-butyl analogues with the goal of observing the effect of the ligand field on the magnetic properties. In the [VTpCl](+), [CrTpCl](+), [CoTpCl], and [NiTpCl] complexes, the magnetic anisotropy arises as a consequence of out-of-state spin-orbit coupling, and covalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…LFDFT includes both dynamical correlation (through the DFT exchange-correlation energy) and non-dynamical correlation (via LF Configuration Interaction). With LFDFT procedure, all customary molecular properties can be calculated, [88][89][90][91][92][93][94] including ZFS parameters, 19,20,95,96 however, its accuracy decreases with increasing metal-ligand covalency. 97 Comparison between experimentally determined and calculated ZFS parameters in PBPY-7…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…LFDFT includes both dynamical correlation (through the DFT exchange-correlation energy) and non-dynamical correlation (via LF Configuration Interaction). With LFDFT procedure, all customary molecular properties can be calculated, [88][89][90][91][92][93][94] including ZFS parameters, 19,20,95,96 however, its accuracy decreases with increasing metal-ligand covalency. 97 Comparison between experimentally determined and calculated ZFS parameters in PBPY-7…”
Section: Mössbauer Spectroscopymentioning
confidence: 99%
“…Therefore, design, control and fine-tuning of the magnetic anisotropy is a challenging task. [13][14][15][16][17][18][19][20][21][22] It is noteworthy to mention that magnetic anisotropy is very sensitive to the surrounding of a central metal ion and is therefore also employed to explore the oxidation states, spin states and coordination modes of transition metal complexes. 23 Examples of systems with very large magnetic anisotropy are complexes of transition metals in linear geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The pair of singly‐occupied e orbitals (SOMOs), nominally 3d xz and 3d yz , is destabilized by σ* interaction with the pyrazole nitrogens, as well as π* overlap with B–H bonds. C 3 v ‐symmetric chloride complex analogues adopt a similar electronic conformation, (e) 4 (a 1 ) 2 (e) 2 ,, wherein the chloride lone pairs are essentially isolobal with the B–H bonds, except that the 3d z ² orbital is relatively destabilized by overlap with the axially‐constrained chloride 3p z orbital , . The η 4 ‐borohydride ligand therefore acts as a six‐electron donor and the [(Tp Me,Me )Ni(η 4 ‐BH 4 )] complex has 20 valence electrons …”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…9 They are essential in the design of single molecular magnets. [17][18][19] The vibronic coupling is responsible for the observation of symmetry-forbidden transitions in spectroscopy, 20 conical intersections in photochemistry, and is indispensable for understanding the spectroscopy of linear molecules. [21][22][23][24][25][26] The cause of any structural distortion of a polyatomic system is due to the JT, RT, PJT effect, or their combination.…”
mentioning
confidence: 99%
“…It has been shown that controlling the geometry of a transition metal complex is the way to chemically control their magnetic properties, particularly that spin-orbit coupling (SOC) could be used to tune the magnetic anisotropy. 18,19 If the SOC is higher, the magnetic anisotropy has a greater value. Knowing the fact that both coordination of the ligands and the partial quenching of the SOC due to JT distortions reduce the magnetic anisotropy from its ideal, the free ion value, the system ([NiCl 3 (Hdabco) 2 ] + , dabco is 1,4-diazabicyclo[2.2.2]-octane), was found in which the bulky dabco axial ligands prevent distortion.…”
mentioning
confidence: 99%